New pregaliellalactonoids from Galiella rufa. (June 2015) - Escobar, Zilma; Williams, Headley; Phipps, Richard; Karunakaran, Deepa; Steele, Jonathan; Sterner, Olov
Graphical abstract: Highlights: Several new pregaliellalactonoids were characterised. The structure of compound 4 is revised. A biogenetic route to 1 involving 6 and/or 7 is proposed. Abstract: An extract of a culture of the fungus Galiella rufa yielded several new derivatives of pregaliellalactone (1 ) that were characterised by NMR and MS experiments. The tetraene 4 has been reported previously, but was in this investigation isolated in sufficient amounts for the determination of the configuration of the C-4/C-5 double bond which is Z, not E . The possibility that any of the new compounds are involved in the biosynthesis of 1 is discussed.